Assessing the compressive and impact behavior of plastic safety toe caps through computational modelling - Rodrigues, Pedro Veiga (2021)
Toe caps are one of the most important components in safety footwear, but have a significant contribution to the weight of the shoe. Efforts have been made to replace steel toe caps by polymeric ones, since they are lighter, insulated and insensitive to magnetic fields. Nevertheless, polymeric solutions require larger volumes, which has a negative impact on the shoe’s aesthetics. Therefore, safety footwear manufacturers are pursuing the development of an easy, low-cost and reliable solution to optimize this component. In this work, a solid mechanics toolbox built in the open-source computational library, OpenFOAM®, was used to simulate two laboratory standard tests (15 kN compression and 200 J impact tests). To model the polymeric material behavior, a neo-Hookean hyper-elasto-plastic material law with J2 plastic criteria was employed. A commercially available plastic toe cap was characterized, and the collected data was used for assessment purposes. Close agreements, between experimental and simulated values, were achieved for both tests, with an approximate error of 5.4% and 6.8% for the displacement value in compression and impact test simulations, respectively. The results clearly demonstrate that the employed open-source finite volume computational models offer reliable results and can support the design of toe caps for the R&D footwear industry.